1995
DOI: 10.5694/j.1326-5377.1995.tb138545.x
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of transfusions of red cells, platelets and fresh frozen plasma

Abstract: Objective: To determine how current hospital practice for transfusions of red cells, platelets and fresh frozen plasma conformed with published criteria. Design: Elaboration of criteria for transfusion from a review of the current literature; and analysis of the medical records of patients receiving transfusions of red cells (200), platelets (215), and fresh frozen plasma (260) during defined time periods in 1993. Setting: A large tertiary care teaching hospital. Outcome measures: Inappropriateness rates for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 20 publications
4
43
2
1
Order By: Relevance
“…In our study, ICU and surgical teams were just as likely to order inappropriate FFP transfusions. Our findings are consistent with previous research (4,5,6,18,19), including some in the critically ill (20,21). Rao and colleagues (20) found that Ͼ20% of critically ill patients are exposed to FFP and that about 40% had high prothrombin time (twice the normal level) as the sole indication for FFP.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, ICU and surgical teams were just as likely to order inappropriate FFP transfusions. Our findings are consistent with previous research (4,5,6,18,19), including some in the critically ill (20,21). Rao and colleagues (20) found that Ͼ20% of critically ill patients are exposed to FFP and that about 40% had high prothrombin time (twice the normal level) as the sole indication for FFP.…”
Section: Discussionsupporting
confidence: 94%
“…Because our focus was on patients receiving FFP, we did not review bleeding or invasive procedures among patients who did not receive FFP. Although our results are consistent with others (4,5,6,18,19), they represent practices in one ICU and may not be appropriate for generalization. However, our results are likely to be valid.…”
Section: Discussioncontrasting
confidence: 66%
“…Their indiscriminate use carries the risk of increased susceptibility to hospital-acquired infections, transmission of infectious diseases, TRALI, increased expenditure and mortality in critically ill patients (3-12) . Several research groups have studied the unnecessary use of blood products (15,16,20-30) . In a study at the Melbourne Royal Hospital, Metz et al observed that 16% of the RBC transfusions were inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In a study at the Melbourne Royal Hospital, Metz et al observed that 16% of the RBC transfusions were inappropriate. Among these, 66 transfusions were considered inappropriate because the physician did not record the indication for transfusion (20) . In our study, 5 requests received by the blood bank did not include an indication.…”
Section: Discussionmentioning
confidence: 99%
“…Despite published guidelines on the use of individual blood products, surveys suggest wide variations in their use [29]. To date, such guidelines have not addressed the use of blood in patients undergoing coronary revascularization who may be at particular risk following transfusion.…”
Section: Limitationsmentioning
confidence: 94%